The synergistic combination of trimetazidine, hypoxen and L-carnitine in endurance sports - Hamid A Merchant (University of Huddersfield Press, 2022)
In 2022 Winter Olympics, a 15-year-old star figure skater got into the limelight of a doping scandal after testing positive for trimetazidine along with hypoxen and L-carnitine, raising questions on their role in high performing endurance sports. This editorial explore the potential mechanisms by which these substances work synergistically in enhancing athletic performance under intense hypoxic (oxygen-deprived) conditions. The trimetazidine can reduce the oxygen demand and may help provide energy to the heart muscles, carnitine could help produce more energy, and hypoxen, can help provide that energy even when the tissues are extremely hypoxic (anaerobic conditions). The drugs, however, pose a health and safety risk to athletes, in particular, the adverse effects on cardiac muscles and potential risks of skeletal muscle disorders such as Parkinsonian symptoms. The practitioners in sports nutrition and physical training are, therefore, advised to reflect on current nutritional practices for enhancing endurance and ethical implications of using these supplements in athletes.